Aspects of multilingualism in European language history - Braunmüller, Kurt, 1948-; Ferraresi, Gisella (Hamburg studies on multilingualism ;, 2003)
This volume gives an up-to-date account of various situations of language contact and multilingualism in Europe especially from a historical point of view. Its ten contributions present newly collected data from different parts of the continent seen through diverse theoretical perspectives. They show a richness of topics and data that not only reveal numerous historical and sociological facts but also afford considerable insight into possible effects multilingualism and language contact might have on language change. The collection begins its journey through Europe in the British Isles. Then i.